Features of non-stenotic carotid plaque on computed tomographic angiography in patients with embolic stroke of undetermined source - Guo, Danling; Lv, Sangying; Wu, Guanzuan; Li, Haifeng; Wei, Bo; Yang, Jianfeng (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Embolic stroke of undetermined source (ESUS) is a subset of cryptogenic stroke constituting a large proportion of acute ischemic strokes. This study aimed to assess the features of non-stenotic carotid plaque (<50%) on computed tomographic angiography (CTA) and to evaluate the association between non-stenotic carotid plaque and ESUS. Methods: From January 1 to December 31, 2019, a total of 60 consecutive patients with primary unilateral ESUS and <50% carotid artery stenosis, as determined using screening ultrasonography, were hospitalized in the Department of Neurology of our hospital. All enrolled patients underwent CTA to determine the composition and morphological features of non-stenotic carotid plaques using consecutive sections in both carotid arteries. The features of these plaques with and without ipsilateral stroke in patients with ESUS were compared. Results: Sixty ESUS images were included in the study, with 85 plaques. Forty-five (52.9%) of these plaques were ipsilateral and 40 (47.1%) were contralateral to the stroke. Compared to that of the contralateral plaque group, the maximum carotid plaque thickness and plaque length of the ipsilateral group were greater (2.1 mm vs 1.5 mm, p=0.03; 20.8 mm vs 12.1 mm, p=0.02); however, there were no significant differences in the degree of luminal stenosis, presence of soft plaque and calcified plaque, and the number of ulcers on the plaque surface between the two groups. Similarly, the number of plaques with thickness >3 mm in the ipsilateral group was greater than in the contralateral group (30 vs 13, p=0.01). A lipid core was more common in individuals with ipsilateral strokes than in those with contralateral strokes (19 vs 7, p=0.02). Regression analysis showed that plaque lipid core area was an independent risk factor for ESUS (odds ratio, 1.92; 95% confidence interval, 1.22–3.04; p=0.03). Conclusions: Non-stenotic carotid plaques could be an etiology of acute ischemic strokes classified as ESUS. The presence of a lipid core was a risk factor in individuals with non-stenotic carotid plaques.